Perbedaan Tingkat Pengetahuan Tentang Kanker Serviks Di Sma Negeri 1 Kartosuro Dengan Sma Pondok Pesantren Modern IslamAssalaam - Ambarsari, Ferina, dr. M. Shoim Dasuki, M.Kes, dr. Anika Candrasari, M.Kes (2014)
Background: cervical cancer is the most common type of malignancy found among women. Because of high incidence of cervikal cancer. Many indonesian woman died. Cervical cancer in indonesia occupied the 2nd place in the order of malignacy in woman is (16 person per 100.000 women). High incidence of cervical cancer in indonesia itself is caused by lack of knowledge and awareness of the dangers of cervical cancer. One of cervical cancer risk factors sex before 20 years old, so that the knowledge about the dangers of having sex before the age of 20 years is very important because it can prevent the occurrence of cervical cancer. The purpose of the research: to determine defferences in the level of knowledge about cervical cancer in SMA 1 Kartosuro with modern Islamic boarding school Assalaam. Research methods: using analytic observational research design with cross sectional approach. Samples taken in purposive sampling and sample generated as many as 100 people are divided into two groups, each group of 50 people. Data were analyzed by T-test for independent tests. Research results: based on the results of the statistical tests of the independent T-test values obtained significant probability (p) = 0.012 thus p 0.05 then Ho < rejected and accepted Ha. Conclusion: there are differences in the level of knowledge about cervical cancer in girls SMA 1 Kartosuro country with girls boarding school Assalaam.